STUDI KRITIS LEGISLASI HUKUM ZAKAT DAN PERWAKAFAN - Nurainum, Nurainum; Fathurahman, H.; Hamzah, Hamzah; Fadila, Anisa Sri (Jurnal Ar-Risalah, 2023)
AbstractThis study examines the study of zakat and waqf legal legislation in Indonesia. This research is purely library research. Data obtained from available literature and documentation, whether in the form of laws or available books, were then analyzed using a historical approach and a statutory approach. Based on the results of the study, it can be concluded that the implementation of zakat and endowment law in Indonesia is seen from its history, starting from the era of independence to the reformation era. The birth of different legal regulations is influenced by the underlying conditions, such as the political motives of the ruling government, economy and religion. The legal position of zakat as a form of increasing the effectiveness of realizing community welfare and poverty alleviation. If so, zakat law legislation is considered necessary, so that people's awareness of zakat will be high and zakat can be used as an alternative to realizing community equality. The position of waqf law as a manifestation of the formality of the traditions of society in Indonesia, especially those who are Muslim, so that they can meet the needs of the times is the duty of the state as a regulator, so that in the form of waqf implementation it can function more as an increase in the socio-economic welfare of the people. Several new provisions on zakat law in Indonesia are different from what is taught in fiqh. Likewise with the new provisions of the law. waqf in Indonesia which is different from what is taught in fiqh, several new provisions in laws and regulations include expanding the parties who can become waqif and nadzir, expanding the types of waqf assets that can be donated, the waqf period does not have to be forever, changes status of waqf objects with clear terms and procedures, as well as detailed management and development of waqf assets.Â Abstrak:Studi ini menelaah studi legislasi hukum zakat dan perwakafan di Indonesia. Penelitian ini murni penelitian kepustakaan. Data yang diperoleh dari literatur dan dokumentasi yang tersedia baik itu berupa undang-undang ataupun buku yang tersedia kemudian dianalisis dengan menggunakan pendekatan historis dan pendekatan yuridis-normatif. Berdasarkan hasil telaahan dapat disimpulkan bahwa Pemberlakuan hukum zakat dan perwakafan di Indonesia di lihat dari sejarahnya di mulai dari era kemerdekaan sampai era reformasi. Lahirnya regulasi hukum yang berbeda-beda dipengaruhi oleh kondisi-kondisi yang melatabelakanginya, seperti motif politik pemerintah yang berkuasa, ekonomi serta keagamaan. Kedudukan hukum zakat sebagai wujud meningkatkan efektivitas mewujudkan kesejatraan masyarakat dan penanggulangan kemiskinan. Jika demikian legislasi hukum zakat dianggap perlu, sehingga kesedaran masyarakat dalam berzakat akan tinggi dan zakat dapat digunakan sebagai alternatif mewujudkan kesejataraan masyarakat. Kedudukan hukum perwakafan sebagai wujud formalitas tradisi masyarakat di Indonesia khususnya yang beragama Islam agar dapat memenuhi kebutuhan zaman merupakan tugas negara sebagai regulator, sehingga dalam wujud pelaksanaan wakaf dapat lebih difungsikan sebagai peningkatan kesejatraan sosial ekonomi umat. Beberapa ketentuan baru hukum zakat di Indonesia yang berbeda dengan dengan apa yang diajarkan dalam fikih. Begitu juga dengan ketentuan baru hukum. perwakafan di Indonesia yang berbeda dengan dengan apa yang diajarkan dalam fikih, beberapa ketentuan baru dalam peraturan perundang-undangan meliputi perluasan pihak-pihak yang bisa menjadi wakif dan nadzir, perluasan jenis harta benda wakaf yang bisa diwakafkan, jangka waktu wakaf tidak harus selamanya, perubahan status benda wakaf dengan syarat dan prosedur yang jelas, serta pengelolaan dan pengembangan harta benda wakaf yang diatur terperinci.